Passing the test: A standardised passing drill provides a valid assessment of cardiorespiratory fitness in senior football players - Shushan, T.; Lovell, R.; McLaren, S. J. (Journal of Sports Sciences, 2026)
This study examined the concurrent and criterion validity of a football-specific intermittent-variable submaximal fitness test (SMFT) as an indicator of cardiorespiratory fitness. Eighteen male senior football players were monitored over a 12-week period using a repeated measures design. Each week, a standardised Y-shape passing drill (practical SMFT) was administered immediately following a 4-min continuous run (criterion SMFT), with exercise heart rate (HRex) measured during both protocols. Laboratory-derived measures of cardiorespiratory fitness were assessed at the start and end of this period. The within-player correlation between HRex from the two SMFTs was large, with a clear improvement in the relationship (U+0394 r ˜0.2) and model fit (U+03C72 = 52.1, p < 0.001; adjusted vs unadjusted model statistics: marginal-R2 = 0.56 vs 0.29, Akaike information criterion = 434.8 vs 477.0, root mean square error = 1.63 vs 2.21%-points of HRmax) after adjusting for passing drill total and high-speed running distances. Adjusted HRex values from the passing drill showed stronger associations (r ˜-0.70 vs -0.35) with maximal oxygen uptake and maximal aerobic speed. A Y-shape passing drill offers a valid and practical assessment of cardiorespiratory fitness within the SMFT framework. We provide a method to guide practitioners in adjusting HRex for external training load, thereby improving agreement with criterion SMFT running protocols.